2018
DOI: 10.1007/s10047-018-1026-5
|View full text |Cite
|
Sign up to set email alerts
|

The use of VV-ECMO in patients with drug dependencies

Abstract: The purpose of this study is to determine the effect of illicit drug and alcohol dependencies on mortality, length of stay, and complications in patients who have been supported with veno-venous extracorporeal membrane oxygenation (VV-ECMO) following respiratory failure not responsive to conventional methods of ventilation. 584 VV-ECMO referrals received at Wythenshawe Hospital were reviewed for evidence of drug dependency. 13 patients were identified as being drug-dependent and having undergone treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Prior investigations involving drug and alcohol dependent patients on VV ECMO did not specify that the inciting underlying diagnosis be the result of an acute intoxication, rather that the patients have an ongoing history of substance use. 7 Similar to our baseline statistics, their drug-dependent group had a lower weight than their non-drug-dependent matched cohort. However, the duration of ECMO was increased by almost 2 days in that drug-dependent cohort, which stands in contrast to our findings.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Prior investigations involving drug and alcohol dependent patients on VV ECMO did not specify that the inciting underlying diagnosis be the result of an acute intoxication, rather that the patients have an ongoing history of substance use. 7 Similar to our baseline statistics, their drug-dependent group had a lower weight than their non-drug-dependent matched cohort. However, the duration of ECMO was increased by almost 2 days in that drug-dependent cohort, which stands in contrast to our findings.…”
Section: Discussionsupporting
confidence: 71%
“…A retrospective study by Stoyle and colleagues demonstrated a small increase in the number of complications in patients with a history of drug or alcohol dependency on VV ECMO compared to those without a history of dependency. 7 While there was no statistical difference in rates of survival, there have been a number of case reports, which demonstrate the effective use of VV ECMO in patients with drug-related respiratory collapse. The etiology of the respiratory compromise is varied, including opioids, cocaine, 8,9 and marijuana cigarettes laced with phencyclidine or formaldehyde.…”
Section: Intoxication and Overdose Should Not Preclude Veno-venous Ex...mentioning
confidence: 99%
“…However, limited experience with the use of percutaneous ECMO in drug-dependent patients has resulted in longer hospital stays and higher rates of complications. [13] Another dilemma the team faced was whether it was ethically the right decision to put this patient on ECMO, knowing that she may face longer hospital stays and poorer postoperative outcomes. Additionally, ECMO would require the allocation of a perfusionist around the clock, which would inevitably result in reducing nearly half the elective and inpatient cardiac operations in our unit.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited experience with the use of percutaneous ECMO in drug-dependent patients has resulted in longer hospital stays and higher rates of complications. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…In this group, civilisation diseases are rare, and if they do additionally occur, they significantly reduce patients' overall chances of survival. In the case of alcoholics, the presence of severe chronic hepatic insufficiency or advanced mental disorders is often sufficient to abandon any invasive procedures [34]. As a result of these circumstances, AD patients are unlikely to be qualified for more sophisticated and invasive ICU procedures.…”
Section: Discussionmentioning
confidence: 99%